Optimization of mycodextran production from efficient fungal in submerged culture - Phichamon Noisuwan (2018)
© 2017, Chiang Mai University. All rights reserved. Mycodextran production from various strains of fungal was reported using modified media composed of different carbon sources from agricultural wastes, grain extracts and a nigeran production (NP) medium. Aspergillus japonicus IFO 4337 had the highest yield of 0.25 g/l when cultured in NP medium and incubated at 28°C with shaking (120 rpm) for 14 days. Optimum medium components and culture conditions for mycodextran production in a shaking flask culture consisted of (% w/v) 3% glucose, 1% NH 4 NO 3 , and pH 5, incubated at 28°C for 7 days, and the highest mycodextran yield of 0.67 g/l. The brown-rice extract and coconut water were the optimal modified media for producing mycodextran and yielded 2.30 and 1.23 g/l, respectively, when incubated at 28°C, 120 rpm for 7 days. Static liquid culturing methods can reduce costs and had 8.3 fold higher yields compared to the shake flask culture. The Plackett-Burman design (PBD) was applied for evaluation of different medium component for mycodextran production by Aspergillus japonicus IFO 4337. Only NH 4 NO 3 is the most effective component with positive significance are selected for further optimization by response surface methodology (RSM).